Evaluation of Four Veterinary Hematology Analyzers for Bovine and Ovine Blood Counts for In Vitro Testing of Medical Devices. Issue 11 (18th April 2016) - Pieper, Ina Laura; Friedmann, Yasmin; Jones, Alyssa; Thornton, Catherine
Abstract: Small affordable automated hematology analyzers that produce rapid and accurate complete blood cell counts are a valuable tool to researchers developing blood‐handling medical devices, such as ventricular assist devices, for in vitro safety assessments. In such studies, it is common to use the blood of large animals such as cattle and sheep. However, the commercially available instruments have not been evaluated for their ability to measure the blood counts of these animals. In this study, we compare, for the first time, four veterinary analyzers for blood counts on bovine and ovine blood samples. We look at ease of use, repeatability and agreement with a view to inform researchers of the benefits of these instruments in routine measurement of ovine and bovine bloods during in vitro testing. Complete blood cell counts and a three‐part differential (granulocytes, monocytes, and lymphocytes) were measured by each of the instruments, and the results compared to those obtained from two additional analyzers used in a reference laboratory. Repeatability and agreement were evaluated using the Bland–Altman method; bias and 95% limits of agreement between the instruments, and between the instruments and two reference instruments, were used to evaluate instrument performance. In summary, there are advantages and disadvantages with all instruments. Of the four instruments tested, the repeatability and agreement was fairly similar for all instruments except one instrument which cannot be recommended for bovine or ovine blood counts.